AI and the BoLC: Streamlining legal translation - Giampieri, Patrizia (Comparative Legilinguistics, 2024)
Artificial Intelligence (AI) applied in the legal field has gained considerable ground in the recent years and is used in many fields, amongst which the legal one is of no exception. This paper wishes to explore the quality of the translation (from English into Italian) of an arbitration clause performed by the ChatGPT chatbot. To do so, the automatically generated target text is post-edited by consulting the BoLC (Bononia Legal Corpus) and the web as corpus in the gov.it Italian governmental domain. General and legal dictionaries are also used. The paper findings report some inaccuracies at word level which are easily tackled by corpus consultation. In view of the results obtained, however, complete reliance upon AI-driven solutions is not recommendable at the time being. Conversely, the use of ad hoc corpora and of targeted web searches are the most feasible and reliable solutions, although time-consuming.